1987
DOI: 10.1177/004728758702600203
|View full text |Cite
|
Sign up to set email alerts
|

Segmenting the Vacation Market by Novelty-Seeking Role

Abstract: Segmenting the Alaska vacation market using novelty-seeking roles resulted in both theoretical and managerial insights. The three novelty-motivated segments differed with respect to travel-group characteristics, behaviors, and attitudes. The results indicated that Cohen's tourist role typology, the social group concept, and Clawson and Knetsch'sfive stage model of the travel experience furnish useful constructs for formulating models of tourism behavior. The segmentation model also yielded actionable informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 9 publications
1
59
1
Order By: Relevance
“…Commonplace or familiar trips occur only when the tourists seek to fulfill specific social demands such as kinship or social interactions (Snepenger, 1987). Dann (1977) also suggests that historical and anecdotal tourist motivation theories could be summed up by the concept of escape.…”
Section: Cultural Distance As a Facilitatormentioning
confidence: 99%
“…Commonplace or familiar trips occur only when the tourists seek to fulfill specific social demands such as kinship or social interactions (Snepenger, 1987). Dann (1977) also suggests that historical and anecdotal tourist motivation theories could be summed up by the concept of escape.…”
Section: Cultural Distance As a Facilitatormentioning
confidence: 99%
“…For example, Shoemaker (1984) observed that travel agents were consulted about routes, accommodation and activities at the destination. Travel agents were also proved to be a useful source of information for older travelers (Gitelson and Crompton 1983;Shoemaker 1984) and the most-used source for tourism at both the individual and group levels (Snepenger 1987). Although there are many tourists who do their own search, they tend to habitually use travel agents to make their bookings.…”
Section: Travel Agentsmentioning
confidence: 99%
“…Many studies have concluded that institutional brochures (Fodness and Murray 1999;Nolan 1976;Raitz and Dakhil 1989;Snepenger 1987;Snepenger et. al.…”
Section: The Relationship Between Use Of Non-media Information Sourcementioning
confidence: 99%
“…The first, behavioural theory, concentrates on the tourist group activities and interactions (Craburn 1989;Smith 1989). Secondly, the theory of cognitive psychology emphasizes tourist values, attitudes, needs, risk-taking behaviour and motivation (Cohen 1979;Snepenger 1987;Citelson & Kerstetter 1990;Nickerson & Ellis 1991;Locker & Perdue 1992;Roel & Fesenmaier 1992). A third theory combines the psychological variables and behavioural roles of the traveller (Cohen 1972;Pearce 1982;Yiannakis & Cibson, 1992;Lee & Crompton 1992;Mo et al 1994).…”
Section: Proposal Of a Framework For Analysing Sport Tourism Consumermentioning
confidence: 99%